Literature Review: Risk Factors For Tuberculosis Incidence In Health Workers In Indonesia - Abdi*, Desi Nur; Erwandi, Dadan (Riwayat: Educational Journal of History and Humanities, 2023)
Tuberculosis (TB) is the 13th leading cause of mortality globally and is the second rank in terms of leading infectious killer after COVID-19 (surpassing HIV and AIDS). Indonesia holds the second-highest number of TB cases worldwide. Health workers are among the high-risk groups for TB infection. This studys objective is to determine the risk factors affecting tuberculosis occurrence among health workers in Indonesia. This research uses the literature review method and involves a thorough review of existing literature from 12 published journals. The literature review outcome underscores a significant correlation between Tuberculosis incidents among health workers and personal aspects, such as smoking habits. Conversely, no significant association was observed between individual factors like age, education, nutritional status, and employment factors such as duration and type of work.